New Treatments for Idiopathic Pulmonary Fibrosis. Issue 6 (November 2016) - Meyer, Keith C.; Modi, Dhruvang
Abstract : Idiopathic pulmonary fibrosis (IPF) is a progressive disease that kills nearly 40, 000 US citizens annually and has a median survival that has been estimated at 3 to 5 years. Most placebo-controlled, randomized clinical trials performed with promising new therapies over the past 15 years have not achieved chosen therapeutic endpoints, but multiple Phase 3 trials with 2 agents, pirfenidone and nintedanib, demonstrated a significant slowing of the forced vital capacity decrease, and these antifibrotic drugs were recently approved by the US Food & Drug Administration as of October 2014 for prescription in the United States. These new therapies are available to patients with IPF, but can cause significant side effects and must be monitored carefully. Many new drugs are also in various phases of clinical trial testing and may provide additional future benefit to patients with this devastating disease. We review recent and ongoing clinical research that seeks to identify new therapies for patients with IPF, and we present a suggested approach to incorporating the recently approved antifibrotic agents into paradigms to treat patients with IPF.